2018
DOI: 10.1038/modpathol.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer: correlation between immunohistochemical subtyping and PAM50 intrinsic subtypes, and the subsequent clinical outcomes

Abstract: Male breast cancer is a rare disease that is still poorly understood. It is mainly classified by immunohistochemistry as a luminal disease. In this study, we assess for the first time the correlation between molecular subtypes based on a validated six-marker immunohistochemical panel and PAM50 signature in male breast cancer, and the subsequent clinical outcome of these different subtypes. We collected 67 surgical specimens of invasive male breast cancer from four different Spanish pathology laboratories. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…A smaller study of 67 MBC from Sanches-Muñjos, doing PAM50 subtyping based on a 50-gene signature also showed an overweight of Luminal B subtype [15]. This means that we will have to be aware that more men are Luminal B, compared to females with luminal type breast cancer [28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A smaller study of 67 MBC from Sanches-Muñjos, doing PAM50 subtyping based on a 50-gene signature also showed an overweight of Luminal B subtype [15]. This means that we will have to be aware that more men are Luminal B, compared to females with luminal type breast cancer [28].…”
Section: Discussionmentioning
confidence: 98%
“…Studies made on intrinsic subtypes based on histopathological criteria show that almost all are of luminal subtype and most often Luminal A compared to Luminal B, although results are conflicting [11,13,14]. Only very few and small studies doing molecular subtype, based on PAM50, showed Luminal B to be more common [15].…”
Section: Introductionmentioning
confidence: 99%
“…Sanchez-Munoz et al confirmed the correlation between IHC and PAM50 intrinsic subtypes in patients with male BC; however, they defined a proportion of patients with HER-2 negative by IHC but HER-2 enriched by PAM50 analyses. [4] Although in female patients with BC, luminal A had a favorable prognosis than luminal B; in our male BC dataset, patients with luminal A and B had similar recurrence pattern and metastatic involvement. EORTC 10085/TBCRC/BIG/NABCG International Male Breast Cancer Program also did not reveal any recurrence-free survival and OS in their dataset among BC subtypes.…”
Section: Discussionmentioning
confidence: 69%
“…[3] Basal-like tumors were rare. [4] The data on HER-2 overexpression by IHC are inconsistent in studies. Two series reported 1.7% and 15% HER-2 positivity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since the rarity of the disease hinders large prospective randomized clinical trials, MBC is significantly less well understood compared to female breast cancer (FBC) (3). Traditionally, MBC has been thought to be similar to post-menopausal FBC, and treatment of MBC has been based upon knowledge from studies with a smaller number of patients and studies of FBC (4,5). Differences between MBC and FBC do, however, exist; for example, MBC more often arises with an underlying germline cancer predisposition and displays a different penetrance compared to FBC (6).…”
mentioning
confidence: 99%